(untitled) (CIPEEX, 2023)
The improper disposal of pharmaceuticals and the incorrect handling and disposal of pharmaceutical waste can pose serious risks to public health and the environment. The present study aims to conduct and describe a systematic review, developed through bibliographic research and documentary analysis of laws, regulations, and standards related to the management of medications and pharmaceutical waste. Its objective was to collect information on the procedures adopted for the disposal of pharmaceuticals at the domestic and industrial levels, along with an analysis of the current legislation. The results indicate a lack of information for the general population regarding the correct disposal methods and suggest the issuance of more specific regulations for the treatment and handling of pharmaceutical industry waste. The development of the present study made it possible to conclude that more effective laws and adequate oversight are necessary to reduce the negative environmental impact caused by pharmaceuticals. Moreover, the present study emphasizes the need for the development of sustainable technologies capable of preventing the arrival of pharmaceutical waste in the environment.